Usefulness of dermoscopy in the diagnosis of lichen ruber planus. - Pisani, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Case report. A 21-year-old young man was first observed due to the presence from 3 months of three circumscribed cutaneous lesions. The most characteristic lesion in the thoracic spine (Fig. 4 and yellow box) was preceded by slight itching and dated from 3 months. Physical examination showed a roughly linear brownish plaque, 2 cm long and 2-4 mm wide, with irregular outline. The other two lesions in the left scapula (Fig. 4 and white box) and left deltoid (Fig. 5 and green box) were rounded papules of 5 and 3 mm in diameter respectively, brownish in color, with characteristics similar to the linear lesion, but with different shape. The presence of a brownish pigmentation led us to examine dermoscopically the lesions. All three papular lesions had overlapping dermoscopic aspects (Fig. 1, 2, 3), i.e. whitish round areas surrounded by thin linear brownish pigmentation regularly distributed radially. A punch biopsy from the linear lesion showed hypergranulosis and degeneration of the basal layer in the epidermis and superficial, band-like lymphocytic infiltrate in the dermis. The histologic and dermoscopic data led to the final diagnosis of lichen ruber planus.